MANHOLE COVER OPENING/CLOSING ASSISTING TOOL, AND MANHOLE COVER STRUCTURE - TERADA AKIHIRO (2023)
To provide a manhole cover opening/closing assisting tool capable of enhancing crime prevention performance of a manhole cover, and a manhole cover structure having high crime prevention performance.SOLUTION: An opening/closing assisting tool for assisting an opening/closing operation of a manhole cover structure comprises: a lock connection portion configured to be connected to a lock main body from an upper surface side of the cover so that a position of the lock main body can be switched; and a tool connection portion configured to enable an opening/closing tool be connected in a state where the lock connection portion is connected to the lock main body in an unlocked position so that the opening/closing operation of the cover can be performed using the opening/closing tool for opening/closing the cover with respect to a frame body.SELECTED DRAWING: Figure 30 【課題】 マンホールの蓋の防犯性能を高めることができるマンホールの蓋の開閉補助具、および防犯性能の高いマンホールの蓋構造体の提供。【解決手段】 マンホールの蓋構造体における蓋の開閉操作を補助する開閉補助具であって、錠本体部の位置の切替えが可能となるように、蓋の上面側から錠本体部に対して連結可能に構成される錠連結部と、蓋を枠体に対して開閉操作するための開閉工具を用いて蓋の開閉操作ができるように、錠連結部が解錠位置の錠本体部に連結した状態で開閉工具が連結可能に構成される工具連結部とを備える。【選択図】図３０